2019
DOI: 10.1186/s13058-019-1153-9
|View full text |Cite
|
Sign up to set email alerts
|

Leptin produced by obesity-altered adipose stem cells promotes metastasis but not tumorigenesis of triple-negative breast cancer in orthotopic xenograft and patient-derived xenograft models

Abstract: Background Breast cancer is the second leading cause of cancer deaths in the USA. Triple-negative breast cancer (TNBC) is a clinically aggressive subtype of breast cancer with high rates of metastasis, tumor recurrence, and resistance to therapeutics. Obesity, defined by a high body mass index (BMI), is an established risk factor for breast cancer. Women with a high BMI have increased incidence and mortality of breast cancer; however, the mechanisms(s) by which obesity promotes tumor progression a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 44 publications
1
50
0
Order By: Relevance
“…In a recent publication, patient-derived xenograft (PDX) model, tumours grown in the presence of obesity-altered adipose stem cells in SCID/beige mice had increased circulating HLA1 + human cells as well as increased numbers of CD44 + CD24 − cancer stem cells in the peripheral blood, the authors concluded leptin produced by obesity-altered adipose stem cells promotes metastasis. Others have found a negative association with BMI and CTC counts using the CellSearch device [31,32]. Further work is needed to assess this correlation between CTCs and BMI.…”
Section: Discussionmentioning
confidence: 95%
“…In a recent publication, patient-derived xenograft (PDX) model, tumours grown in the presence of obesity-altered adipose stem cells in SCID/beige mice had increased circulating HLA1 + human cells as well as increased numbers of CD44 + CD24 − cancer stem cells in the peripheral blood, the authors concluded leptin produced by obesity-altered adipose stem cells promotes metastasis. Others have found a negative association with BMI and CTC counts using the CellSearch device [31,32]. Further work is needed to assess this correlation between CTCs and BMI.…”
Section: Discussionmentioning
confidence: 95%
“…In a recent publication, patient-derived xenograft (PDX) model, tumours grown in the presence of obesity-altered adipose stem cells in SCID/beige mice had increased circulating HLA1 + human cells as well as increased numbers of CD44 + CD24cancer stem cells in the peripheral blood, the authors concluded leptin produced by obesity-altered adipose stem cells promotes metastasis. Others have found a negative association with BMI and CTC counts using the CellSearch device [31,32]. Further work is needed to assess this correlation between CTCs and BMI.…”
Section: Discussionmentioning
confidence: 95%
“…The treatment of breast cancer MCF-7 cell line with leptin leads to a remarkable increase in the expression of EMT markers (including vimentin and Snail) along with a downregulation of the epithelial marker E-cadherin ( 62 ). Besides, leptin secreted by adipose stem cells is demonstrated to promote the mesenchymal phenotype in triple-negative breast cancer (TNBC) cells through increased expression of TWIST1, Serpine1, and SNAI2 ( 63 ). Mouse mammary tumor virus (MMTV)-Wnt-1 transgenic mice, which develop spontaneous breast cancer under a diet-induced obesity regimen, present increased leptin production, upregulated EMT gene expression, and reduced survival ( 64 ).…”
Section: Bmas and Mechanisms Associated With Cancer Cells Migration Amentioning
confidence: 99%